Potential protective effects of bilirubin following the treatment of neonatal hypoxic-ischemic encephalopathy with hypothermia therapy. Issue 6 (4th June 2019) - Zou, Liangyan; Yuan, Hao; Liu, Qing; Lu, Chunmei; Wang, Laishuan
Abstract : Background : Therapeutic hypothermia (TH) is the standard therapy for hypoxic-ischemic encephalopathy (HIE) and is associated with a wide range of physiological changes.Objective : We re-evaluated the effects of HIE and TH on bilirubin measurements following HIE in a center involved in the China cooling randomized controlled trial (RCT).Methods : Serial serum bilirubin concentrations measured during the first week of life were compared among the HIE + NT (normothermia) group, HIE + TH treatment group and control group (without HIE). Survivors of HIE were followed and assessed at approximately 2 years of age, and the results were correlated with peak bilirubin levels during the first week of life.Results : One hundred and thirty-eight infants were available for analysis. Significantly lower bilirubin levels were recorded in the HIE + NT group than in the controls ( P <0.05). Significant differences were not observed among the patients in the HIE + NT group (mild to severe) or between the HIE + TH group and the HIE + NT group at any time point ( P >0.05). The peak serum bilirubin concentrations recorded at 96 h of age showed a good correlation with the results of the Bayley Scales of Infant and Toddler Development, third edition (BSID-III) ( P =0.02).Conclusion : Bilirubin potentially exerts a neuroprotective effect during the first week of life, and low temperature does not affect the possible antioxidant function of bilirubin during TH following HIE.